Religious Attendance and Cancer Screening Behavior - Kretzler, Benedikt; König, Hans-Helmut; Hajek, André (Frontiers in Oncology, 2020)
Background: Cancer is one of the most important health problems worldwide. Preventive examinations proved to be effective in tackling that issue, but their degree of utilization is not adequate. Thus, research is making efforts to reveal its determinants. It has been shown that religion is associated with several health outcomes, so that the aim of our study is to analyze the association between religious attendance and participation in cancer prevention. Methods: Data were derived from the fifth wave of the German Ageing Survey (DEAS), a nationally representative, prospective cohort study. Participants are community-dwelling Germans aged 40 years and older. Our main independent variable was the frequency of attendance in religious services, and the dependent variable was participation in cancer screening. As covariates, we included factors from the Andersen behavioral health services utilization model. Multiple logistic regressions were used. In our sensitivity analysis, logistic regressions were performed stratified by religious group (Roman Catholic Church; Protestant Church; not belonging to any religious group). Results: Our model showed that attendance in religious services once a week, one to three times a month, several times a year or less often was significantly associated with an increased likelihood of participating in preventive cancer screening, than never participating in religious services. Moreover, the sensitivity analysis revealed that all these associations remained significant for the Catholic subsample, but neither for the Protestant, nor for the non-religious group. Discussion: This study found a link between a higher frequency of attendance in religious services and an increased likelihood of participating in cancer screenings. This is important to address individuals at risk for underuse of cancer screenings.